The Role OF READING COMPREHENSION IN DEVELOPING OTHER LANGUAGE SKILLS - ABDUL KAREEM LAZIM; ALA’ HUSSEIN ODA ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
An important principle of structural linguistics is that the primary medium of language is oral : speech is language. That’s why speech has a priority in language teaching. Richards and Rodgers (19986: 49) believe that language is speech, not writing ….A language is a set of habits … teach the language, not about the language. Recently, there is a trend in the teaching of foreign languages which advocates the prime importance of teaching reading as a receptive skill before the other productive skills. Gray and Gray (1982: 62) tell us that. The most effective way to teach a foreign language is by providing a substantial base of receptive competence (listening and reading) before attempting to teach productive skills. Hence, the presentation of language through reading passages (with appended comprehension questions) is a well – established and familiar practice. But, learning to read does not precede comprehension; they are both part of the same process. From the beginning, the teacher’s aim should be to go beyond mere words calling and to get an answer from the learner that indicates his understanding.